RETRACTED: Therapeutic interventions impact brain function and promote post-traumatic growth in adults living with post-traumatic stress disorder: A systematic review and meta-analysis of functional magnetic resonance imaging studies - Pierce, Zachary P.; Johnson, Emily R.; Kim, Isabelle A.; Lear, Brianna E.; Mast, A. Michaela; Black, Jessica M. (Frontiers in Psychology, 2023)
Introduction The present systematic review and meta-analysis explores the impacts of cognitive processing therapy (CPT), eye movement desensitization and reprocessing (EMDR), and prolonged exposure (PE) therapy on neural activity underlying the phenomenon of post-traumatic growth for adult trauma survivors. Methods We utilized the following databases to conduct our systematic search: Boston College Libraries, PubMed, MEDLINE, and PsycINFO. Our initial search yielded 834 studies for initial screening. We implemented seven eligibility criteria to vet articles for full-text review. Twenty-nine studies remained for full-text review after our systematic review process was completed. Studies were subjected to several levels of analysis. First, pre-and post- test post-traumatic growth inventory (PTGI) scores were collected from all studies and analyzed through a forest plot using Hedges’ g. Next, Montreal Neurological Institute (MNI) coordinates and t-scores were collected and analyzed using an Activation Likelihood Estimation (ALE) to measure brain function. T-scores and Hedges’ g values were then analyzed using Pearson correlations to determine if there were any relationships between brain function and post-traumatic growth for each modality. Lastly, all studies were subjected to a bubble plot and Egger’s test to assess risk of publication bias across the review sample. Results Forest plot results indicated that all three interventions had a robust effect on PTGI scores. ALE meta-analysis results indicated that EMDR exhibited the largest effect on brain function, with the R thalamus (t = 4.23, p < 0.001) showing robust activation, followed closely by the R precuneus (t = 4.19, p < 0.001). Pearson correlation results showed that EMDR demonstrated the strongest correlation between increased brain function and PTGI scores (r = 0.910, p < 0.001). Qualitative review of the bubble plot indicated no obvious traces of publication bias, which was corroborated by the results of the Egger’s test (p = 0.127). Discussion Our systematic review and meta-analysis showed that CPT, EMDR, and PE each exhibited a robust effect on PTG impacts across the course of treatment. However, when looking closer at comparative analyses of neural activity (ALE) and PTGI scores (Pearson correlation), EMDR exhibited a more robust effect on PTG impacts and brain function than CPT and PE.